Validation of the face-name pairs task in major depression: impaired recall but not recognition - Smith, Kimberley J.; Mullally, Sinead; McLoughlin, Declan; O'Mara, Shane M. (Frontiers in Psychology, 2014)
Major depression can be associated with neurocognitive deficits which are believed in part to be related to medial temporal lobe pathology. The purpose of this study was to investigate this impairment using a hippocampal-dependent neuropsychological task. The Face-Name pairs task was used to assess associative memory functioning in 19 patients with major depression. When compared to age-sex-and-education matched controls, patients with depression showed impaired learning, delayed cued-recall and delayed free-recall. However, they also showed preserved recognition of the verbal and nonverbal components of this task. Results indicate that the face-name pairs task is sensitive to neurocognitive deficits in major depression.